The Transdisciplinary Model of Evaluation - Chris L. S. Coryn; John A. Hattie (The Evaluation Center at Western Michigan University, 2006)
The transdisciplinary view, or model, of evaluation requires an understanding of how and why evaluation developed from a practice to a highly skilled, professional practice to a field-specific discipline, and finally to an autonomous discipline and transdiscipline, much like ethics, statistics, and measurement (Scriven, 2003). This understanding becomes known from the transdisciplinary model's three primary characteristics that make it a transdiscipline, which are: epistemological;political; and disciplinary (Scriven, 1993).